ANALISIS KEBUTUHAN DAN SEBARAN GURU IPS SMP DI KECAMATAN BELITANG TAHUN 2014 - Andri Wijaya; Buchori Asyik; Rosana Rosana (JPG (Jurnal Penelitian Geografi), 2015)
This research aims to get information(1) the social study teachers need, (2) the suitability of social study teacher to the academic qualification, and (3) the distribution of social study teacher in Belitang Sub-district. The study employed descriptive research design with the population are 22 social study teachers in junior high school of Belitang Sub-district. The collecting data techniques used were observation, questionnaire, and documentation techniques.Data analysis technique is using calculation of teachers need formulation. The result of the research shows(1) the social study teachers need in junior high school of Belitang Sub-district as many as 16 teachers, where 1 junior high schools belong to the enough category, and 8 junior high school belongs to the less category, (2) from the total number of 22 social study teachers, 10 social study teachers are graduated from social study education and the 12 social study teachers are graduated from non-social study education, (3) the distribution of social study teacher in Belitang Sub-district is in group Gumawang village.Penelitian ini bertujuan untuk memperoleh informasi (1)kebutuhan guru IPS, (2) kesesuaian guru IPS dengan kualifikasi akademik, dan (3) sebaran guru IPSpada SMP di Kecamatan Belitang. Penelitian ini menggunakan metode penelitian deskriptif dengan populasi 22 guru IPS pada SMP di Kecamatan Belitang. Teknik pengumpulan data yang digunakan teknik observasi, teknik kuesioner,dan teknik dokumentasi. Teknik analisis data menggunakanrumus perhitungan kebutuhan guru.Hasil penelitian menunjukkan (1) kebutuhan guru IPS pada SMP di Kecamatan Belitang sebanyak 16 guru, dimana 1 SMP termasuk dalam kategori cukup, dan 8 SMP berkategori tidak cukup, (2) dari 22 guru IPS, 10 guru IPS lulusan S1 Pendidikan Jurusan IPS dan 12 guru lulusan S1 non Pendidikan Jurusan IPS, (3) sebaran guru IPS di Kecamatan Belitang mengelompok pada desa Gumawang.Kata kunci:kebutuhan, kualifikasi akademik, sebaran